A ausência física e afetiva do pai na percepção dos filhos adultos - Damiani, Camila Ceron (Universidade do Vale do Rio dos Sinos, 2014)
Paternal absence is a subject not well known in the national academic scope, despite influencing children’s and teenagers’ affective, cognitive and social development. Important repercussions of this absence also occur in family functioning. Thus, this work investigates the paternal’s physical and emotional absence beyond childhood and adolescence, addressing adults offspring’s perception about this aspect, more specifically, identifying adults’ feelings and experiences on this condition nowadays. Four adults ranging 25 to 40 years old, patients of psychologists who work in a psychology clinic, located in Caxias do Sul / RS, were part of this qualitative study of exploratory nature. All of them have in common the perception of paternal absence, with origin both physical and emotional, as something that continues to bring repercussion in adulthood. A semi-structured interview and the qualitative analysis of content for the discussion of data were used as instruments. To this, a literature review was conducted regarding the paternal absence during the development of children and adolescents in order to better understand the topic. Among the main results, it is highlighted the impact of this distance, being it physical and/or emotional, reflected in feelings of devaluation, abandonment, loneliness, insecurity, low self-esteem and difficulties in relationships which begin to be perceived in childhood and continue interfering in the development trajectory in the adulthood.
Keywords: Paternidade; Relações pai-fiho; Relações familiares; Parentalidade; Paternity; Parent-child relationships; Family relationships; Parenting